(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Light shelves represent a quintessential passive design typology, traditionally utilized to augment daylight penetration while simultaneously mitigating glare to enhance interior visual ergonomics; however, conventional static configurations often fail to recalibrate in response to the stochastic fluctuations of solar geometry, particularly in tropical latitudes like Jakarta, Indonesia, where high solar altitudes persist. This study investigates the efficacy of a revolving light shelf system in optimizing indoor illuminance uniformity through DIALux Evo 8.2 simulations, evaluating rotational increments of ±15?, ±30?, and ±45? across four cardinal orientations over five diurnal intervals. The empirical results demonstrate that dynamic adaptability significantly enhances lighting uniformity and facilitates adherence to standardized illuminance thresholds, with the most profound performance gains observed on the east and west facades where solar azimuth and altitude vary most significantly. Conversely, the north and south elevations exhibited relatively stabilized metrics, requiring minimal angular adjustments to maintain optimal conditions. Ultimately, these findings underscore the imperative of integrated, responsive fenestration systems in tropical climates to reduce reliance on supplementary artificial lighting and provide a foundational framework for future automated building management architectures.